Blueprints for reform (Oxford University Press, 1998)
Serious efforts to reform the K-12 science curriculum in this country require an understanding of the entire system of education. To gain this perspective, Project 2061 of the American Association for the Advancement of Science commissioned experts to report on a dozen areas of education. Blueprints for Reform is a summation of these reports that offers teachers, parents, policymakers, and business leaders a focused starting point for their exploration of the education system and its response to reform. Project 2061 offers new insights about how science education fits into the education system as a whole and how to make meaningful changes that will last. Blueprints looks beyond quick fixes and short-term gains to focus on preparing today's children for life in the 21st century.